Analisis Implementasi Transformasi Digital Oleh PT. Gapura Angkasa Di Bandar Udara Internasional Soekarno-Hatta - Mohamad Trisandi H. Uri; Djoko Widagdo (Jurnal Multidisiplin Indonesia, 2023)
This research aims to find out the process of developing the concept of digitalization and solutions by PT Gapura Angkasa in dealing with obstacles during the process of implementing digital transformation at Soekarno-Hatta International Airport. This research was conducted on February 9, 2023 to February 16, 2023 at Terminal 3 Ultimate of Soekarno-Hatta International Airport. Research data was obtained from the Check-In Counter operational section by including observation of facilities and infrastructure, interviews with the Supervisor of the Check-In Counter section, and digging deeper into the software which is currently entering the development stage. Some facilities and infrastructure such as the Self Check-In Machine, Travelin App, and Digital Wayfinding can be fully used by Passenger but there are still several System Errors so that they still require further assistance or confirmation to the responsible one. While infrastructure such as Face Recognition Camera, and E-KTP Reader are still in the Alpha Testing stage where some of these devices are tested internally and cannot be tested directly on Passenger. The quality of infrastructure and human resources is still one of the main factors behind the adaptation of the latest innovations in Indonesian aviation, and currently Gapura Angkasa is still in the stage of providing education to Passengers regarding the regulations that apply in the airport environment and Gapura Angkasa also in the stage of adapting the Standard Operating Procedure and Standard Use of Hardware & Software socialized by Angkasa Pura to the Soekarno-Hatta International Airport Stakeholders. Another step that can be taken by Gapura Angkasa is to fulfill basic needs such as speed & accuracy of information, feasibility of devices, increasing Human Resources so as to produce Operators who are experts in their fields.